Operation optimisation study for CCGT power plant. - Chen, Yuzhi (Cranfield University, 2018)
A major concern for the power generation industry is to obtain a maximum economic benefit without over-consuming the remaining life of the gas turbine hot section. This study explored a methodology to support decision making for operational optimisation of a combined cycle gas turbine (CCGT) power plant. There is no published algorithm for modelling a parallel dual pressure, once-through steam generator (OTSG), nor any proposed method for OTSG degradation diagnosis and how the degradation affects OTSG performance. What is more, few publications were found for optimisation existing power plant operation considering gas turbine creep life. This study presents a new thermodynamic algorithm to simulate the thermodynamic performance of parallel dual pressure OTSG. In this study, a novel gas path diagnostic method for an OTSG based on the Newton-Raphson method was developed to predict the OTSG degradation caused by fouling. A daily operation decision support platform for this existing power plant is proposed that models CCGT performance, creep life, emissions, economics, and provides a basis for decision-making based optimised results. The OTSG performance model is applied to an OTSG operating in a CCGT power plant at Manx Utilities on the Isle of Man, United Kingdom to demonstrate the effectiveness of the simulation method. A comparison between predicted OTSG performance and OTSG field data showed that the proposed model offers good prediction accuracy when simulating OTSG performance for both design and off-design points. The OTSG diagnostic system was applied to a model OTSG to test its effectiveness. The impact of measurement noise on the diagnostic accuracy was also analysed and discussed. A comparison between predicted and implanted degradation of a model OTSG demonstrated that the results were satisfactory, and the method is promising. Moreover, the diagnostic analysis of an OTSG based on real measurement has further proved that the proposed diagnostic method works well. This simulation will recommend to the plant operator optimal operation schedules taking into consideration thermo-economics and lifing, under conditions of variation of power demand, electricity price, ambient conditions and gas turbine engine health states. It will suggest the more severely degraded engine should run at a relatively lower power setting to decrease creep life consumption. The established power plant optimisation framework will assist power plant operators to decide the total power output and power split between generators based on an optimisation system that considers both immediate economic benefit and life considerations. It will help existing power plant to adjust daily operation to achieve better thermoeconomic and lifing benefits. The outcome of this research will be useful for industrial CCGT power generation.
Keywords: Creep life; decision-making; diagnostic; economics; emission; gas turbine; once-through steam generator; optimisation; performance; simulation; steam turbine; thermoeconomic